国际中文教育领域的超语研究现状及发展趋势：基于SSCI 期刊的分析 - Yijie Wang; Shuang Zhang; Yue Jiang; Chili Li (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
Translanguaging is one of the foci in international linguistics studies. Recently, there is a heat in learning Chinese with the increasing influence of Chinese language in the international area. The present paper synthesized the developmental trajectory, hotspots and future trend of research on translanguaging in international Chinese education based on SSCI-indexed journal articles sourced from Springer, Cambridge, Oxford and Web of Science. It has been found that 1) there is an incremental trend in translanguaging research in international Chinese language education which falls into three stages; 2) there is no close tie of cooperation among researchers and institutions in terms of space distribution with Macao Polytechnic University, Dublin City University, and University of Copenhagen as the institutions that have the most publication number in this field; 3) a multiple hotspots were identified as follows: the application of translanguaging in international Chinese language education, translanguaging pedagogy and diasporic community, Chinese language teaching and global textbooks, cultural comprehension and language policy, and others; 4) the developing trajectory of translanguaging research in international Chinese language education falls into the exploratory period, slow development period, quickening development period, and rapid development period; 5) the emerging keywords like bilingual education, diasporic community, language choice reflected the changes of attention to translanguaging research in international Chinese language education. These changes might exert far-reaching influence on language education, policy, society and culture.